Adjective in Russian and Turkmen Languages: Linguistic and Methodical Aspects - Винниченко, С. Д.; Куллыева, Марал А.; Иванова, Т. А. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
Comparative study of two languages and teaching Russian taking into account specifics of a native language is the key to successful learning in a foreign-language class. The article demonstrates a close dependence of the adjective on the noun in the Russian language and connection by adjoining type in the Turkmen language; points out the absence of external indicators and distinction from other parts of speech, mainly in lexical meaning and a position in the sentence in contrast to Russian adjectives where endings play a more important role. Adjective usage in Russian in pre- and post- positions to the noun it defines is different from Turkmen where transposition is impossible because of its breaking word order and words relationship in a sentence. The article cites Turkmen words from the name category, which could be determined as adjectives according to their semantics. Existence of both the full and the short forms of qualitative adjectives in Russian does not find its analogue in Turkmen, where qualitative adjectives correspond to non-derivative adjective mostly. The article demonstrates correspondence of Russian relative adjectives to a combination of two nouns, where a first noun acts as an attribute and a second noun acts as a determinant, in Turkmen. Such category as possessive adjectives are absent in Turkmen and nouns in genitive case are used instead of them.